2012
DOI: 10.1007/s10508-012-9915-9
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Role of Conditioning in Sexual Orientation

Abstract: The effects of learning on sexual orientation are rarely addressed in the literature. At the very least, such processes provide a means of elaborating upon orientation predispositions. Some aspects of our mates may inherently elicit a sexual response, but other attributes do so only after sexual experience with them. Animal research shows robust, direct effects of conditioning processes on partner preference with a few studies showing plasticity in preference for sex of partner. Descriptive research in humans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 106 publications
0
18
0
Order By: Relevance
“…The origins of this increased interest in sex and the origins of bisexual or same-sex sexual orientations as well as the origins of many of the powerful urges to engage in behaviors such as exhibitionism (Swindell et al, 2011) or to use objects sexually (O'Keefe et al, 2009;Stroebel et al, 2010) can be explained as arising from early childhood experiences through the synergistic actions of critical period learning, sexual imprinting, and conditioning (for reviews see Hoffman, 2012;Pfaus et al, 2012). Obtaining a careful history of early sexual experiences in clients seeking help because of symptoms of sexual addiction or paraphilias may provide insight into the origins of the presenting symptomatology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The origins of this increased interest in sex and the origins of bisexual or same-sex sexual orientations as well as the origins of many of the powerful urges to engage in behaviors such as exhibitionism (Swindell et al, 2011) or to use objects sexually (O'Keefe et al, 2009;Stroebel et al, 2010) can be explained as arising from early childhood experiences through the synergistic actions of critical period learning, sexual imprinting, and conditioning (for reviews see Hoffman, 2012;Pfaus et al, 2012). Obtaining a careful history of early sexual experiences in clients seeking help because of symptoms of sexual addiction or paraphilias may provide insight into the origins of the presenting symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in same-sex and bisexual orientations and behaviors in adult survivors of sister-brother incest would at first glance appear to be paradoxical since conditioning resulting from sexual experiences with the sister would be expected to lead to a heterosexual orientation , Bickham et al, 2013 for reviews see Hoffman, 2012;Pfaus et al, 2012). However, as shown by the data from the logistic and multiple linear regressions in the present article, the mechanism leading to the adult same-sex or bisexual orientations and behaviors involves two steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several notable attempts to condition sexual arousal in humans (see Hoffmann, 2012). Rachman (1966) and Rachman and Hodgson (1968) found that following pairing with erotic visual slides, a pair of women's boots was able to elicit erections in men.…”
Section: Black Wallmentioning
confidence: 99%
“…Likewise, sexual behavior is based on sexual arousal, exploring opportunities, and reward-seeking (Pfaus et al, 2012). Furthermore, men can misattribute their arousal to a different source, at least temporarily (Hoffmann, 2012). For example, they can misattribute residual arousal from physical exercise to sexual stimuli and therefore experience enhanced sexual arousal to these stimuli (Cantor, MALE BISEXUAL AROUSAL AND CURIOSITY 28!…”
Section: High Sexual Curiosity and Bisexual Arousalmentioning
confidence: 99%